Chemical Equilibrium and kinetic study of the esterification of acrylic acid with butanol catalysed by sulfonated expanded polystyrene - Muhammad Ridzuan, Kamaruzaman (2015)
The wastewater containing low concentration (4-10 wt %) of acrylic acid (AA) was treated by incineration since it is very toxic to the organism if it is discharged to the environment. This valuable compound can be recovered using one of the promising methods, the esterification of the diluted AA with alcohol. The sulfonated expanded polystyrene (SEP) from waste expanded polystyrene is a good catalyst to catalyse the esterification of AA with butanol (BuOH). The production of this catalyst can have high impact in environment since the waste polystyrene is huge environmental issues. The SEP was synthesised via the sulfonation of waste expanded polystyrene using sulphuric acid (H2SO4) at 378 K. The slurry obtained after 2 hour of sulfonation was transferred into water and washed with sodium hydroxide, acid hydrochloric and excess water before dried at 343 K. The SEP has a rough surface with minute cracks, can withstand up to 403 K and density of 1.2790 g/cm3. The swelling effect in SEP helps the reactant access the active sites. The activity and kinetic study for this esterification reaction was carried out in batch system. The effect of various parameters that affecting conversion and yield such as stirring speed, initial molar ratio of AA to BuOH, catalyst loading, temperature and initial water content were studied. The reaction was more sensitive to temperature as compared to other parameters. The best conversion and yield obtained at molar ratio AA to BuOH of 1:3, catalyst loading of 10 wt% and temperature of 353 K were 92% and 75% respectively. The yield of butyl acrylate decrease with the increase of initial water content in the reaction mixture because water shifts the reaction equilibrium to reactants, blocked the reactants from accessing active sites and increase polymerisation on the SEP surface. Nevertheless, the SEP can be regenerated easily using sulphuric acid. The experimental kinetic data was correlated to the several kinetic models which were pseudo-homogeneous (PH), Eley-Rideal (ER) and Langmuir Hinshelwood Hougen Watson (LHHW) model. The activation energy is 73.6 kJ/mol. The best fitted model for the main esterification reaction was shown by the non-ideal ER I model. Taking the polymerisation into account, the experimental data are more comparable with the predicted data